2016
DOI: 10.1186/s12645-016-0018-5
|View full text |Cite
|
Sign up to set email alerts
|

Trends in targeted prostate brachytherapy: from multiparametric MRI to nanomolecular radiosensitizers

Abstract: The treatment of localized prostate cancer is expected to become a significant problem in the next decade as an increasingly aging population becomes prone to developing the disease. Recent research into the biological nature of prostate cancer has shown that large localized doses of radiation to the cancer offer excellent long-term disease control. Brachytherapy, a form of localized radiation therapy, has been shown to be one of the most effective methods for delivering high radiation doses to the cancer; how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 105 publications
0
11
0
Order By: Relevance
“…The thiourea derivatives (5a and 5b) exhibited robust inhibitory activity against DU 145 and PC-3 but they remained relatively weak against LNCaP. LnCaP is an androgen-responsive cell line, but the canonical androgen pathway does not work for PC-3 and DU145 cells (Marchiani et al, 2010), indicating that thiourea derivatives might target a different proliferation pathway other than the androgen pathway. As compound 5a was more effective against PC cell lines compared with compound 5b, we selected compound 5a for further action of mechanism studies.…”
Section: Compound 5a Reduces the Cell Proliferation Rate And Cfu Abmentioning
confidence: 99%
See 1 more Smart Citation
“…The thiourea derivatives (5a and 5b) exhibited robust inhibitory activity against DU 145 and PC-3 but they remained relatively weak against LNCaP. LnCaP is an androgen-responsive cell line, but the canonical androgen pathway does not work for PC-3 and DU145 cells (Marchiani et al, 2010), indicating that thiourea derivatives might target a different proliferation pathway other than the androgen pathway. As compound 5a was more effective against PC cell lines compared with compound 5b, we selected compound 5a for further action of mechanism studies.…”
Section: Compound 5a Reduces the Cell Proliferation Rate And Cfu Abmentioning
confidence: 99%
“…While prostatectomy followed by radiation therapy is the standard therapy in clinics for early diagnosed cases (Sriprasad, Feneley, & Thompson, ), patients with advanced stage disease remain incurable due to resistance to chemotherapy, acquired androgen‐refractory phenotype and inefficient radiation therapies (Jarvis, Nelius, Martinez‐Marin, Sennoune, & Filleur, ; Oudard, ; Seruga, Ocana, & Tannock, ). Treatment at late stage of PC could only be possible by combining surgical removal, radiotherapy and chemotherapy options based on clinical priority to monitor adverse outcomes (Nicolae, Venugopal, & Ravi, ; Teply & Hauke, ). Although heterogenous nature of PC restricts the treatment, chemotherapy is generally considered as a prior treatment regimen with both adjuvant and neo‐adjuvant options (Beer & Raghavan, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, we previously reported that the absolute differences in baseline scores between men enrolled in the CEASAR study who completed the baseline survey before versus after starting treatment were very small (range, 1‐3 points), and the Prostate Cancer Outcome Study validation study demonstrated most men accurately recall prediagnostic function 6 months after prostate cancer diagnosis 36,37 . Finally, this study did not account for the use of biodegradable rectal spacers, preoperative magnetic resonance imaging, or other technical advancements for LDR boost 38,39 . As such, the addition of biodegradable rectal spacers may lead to decreases in bowel toxicity, and preoperative magnetic resonance image planning allows better urethral delineation, which may translate to improved urinary toxicity.…”
Section: Discussionmentioning
confidence: 93%
“…36,37 Finally, this study did not account for the use of biodegradable rectal spacers, preoperative magnetic resonance imaging, or other technical advancements for LDR boost. 38,39 As such, the addition of biodegradable rectal spacers may lead to decreases in bowel toxicity, and preoperative magnetic resonance image planning allows better urethral delineation, which may translate to improved urinary toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy ☆ Research Institution: Department of Oncology, University of Calgary, Tom Baker Cancer Centre, 1331-29 ST NW, Calgary, Alberta, Canada T2N 4N2. of registration of different MRI sequences with the live trans-rectal ultrasound (TRUS) images also remains doubtful despite use of deformable registration [26]. Other imaging modalities have been used instead of MP-MRI for dose compensation at the time of LDR brachytherapy.…”
Section: Introductionmentioning
confidence: 99%